PHENOTYPE-GENOTYPE AND PEDIGREE ANALYSIS OF ISOLATED HYPOSPADIAS PATIENTS - Vikawati, Nura Eky; Santosa, Ardy; Juniarto, Achmad Zulfa; Faradz, Sultana MH (Indonesian Urological Association, 2018)
Objective: Hypospadias is a malformation in urethra which has many range of severity. A patient with Isolated hypospadias (IH), a mild disorder of sex development (DSD) has a hypospadias phenotype only. Hypospadias is considered as multifactorial disease in which genetic factors contribute to its development. Chromosome analysis in DSD including hypospadias is conducted for gender assignment and other possible genetic contributions. This analysis solely could not elucidate all genetic causes of hypospadias. Polymorphism of V89L in SRD5A2 is suggested as one of genetic risk factors of hypospadias. To determine the genetic risk factor and pattern of inheritance, a good pedigree construction is required. Material & methods: 35 eligible subjects with IH admitted to Center for Biomedical Research (CEBIOR) during 2012-2015 were randomly selected. 35 normal male as control were included in this study. Data on three generation pedigrees were collected from medical records in 35 affected subjects. Chromosome analyses were done by using G-banding technique. Polymorphism analysis of V89L in SRD5A2 gene was done using PCR-RFLP technique in all samples. Results: From the 35 affected subjects, the most frequent phenotype was penile hypospadias (47%), a pair of twins were monozygotic and one had a cousin diagnosed with urogenital abnormalities (i.e micropenis and chordae). All subjects had 46,XY chromosome. No chromosomal aberration was found. No positive correlation between polymorphism of V89L in SRD5A2 and risk of hypospadias (PR of CC+CG vs GG=1.0, 95% CI: 0.342−2.921, p value=1.0). Conclusion: The pedigree data from our study implies tendency of genetic involvement in hypospadias cases. There were no chromosomal aberrations in hypospadias cases. The finding on polymorphism of V89L in SRD5A2 gene does not support that of previous studies.